FACTORS AFFECTING PUBLIC COMPLIANCE TO PAY TAXES IN BANDUNG CITY - Hanifah, Wardah; Bagja, Hafied Noor; Istihana, Dini; Islamiah, Saffanah; Loe, Eufilha Afonso Nunes; Afaratu, Riyan Ronald (CENTRAL ASIA AND THE CAUCASUS, 2022)
Taxpayer compliance refers to the effort made by a taxpayer to comply with his or her obligation to pay taxes and report his or her tax obligations in accordance with applicable regulationsOne of the significant factors affecting taxpayer compliance is that many taxpayers complain when paying taxes because the services provided by the tax authorities are inadequate. This results in complaints from taxpayers when completing their tax affairs, which ultimately increases non-compliance with tax obligations.The purpose of this research is to learn about taxation, the factors that influence people’s compliance with tax obligations, and the penalties associated with tax evasion.The research method used in this study was quantitative, as the research data were in the form of numbers and were analyzed using statistical techniques.The authors are interested in researching “Factors Affecting Public Compliance to Pay Taxes in Bandung City.”